Kuninkaita maanpaossa II - Daudet, Alphonse, 1840-1897; Leino, Kasimir, 1866-1919 (Salt Lake City, UT : Project Gutenberg, 2008)
"Kuninkaita maanpaossa II" by Alphonse Daudet is a novel written in the early 20th century. This work likely falls into the genre of historical fiction, exploring themes of royalty, exile, and intrigue against a backdrop of societal and economic challenges. The narrative may center around characters tied to nobility, particularly focusing on King Kristian II and his entanglements as they navigate their precarious situations while highlighting their relationships with other key figures, like Senora and Tom Lewis. The opening of the story sets the scene in an office where J. Tom Lewis exudes a buoyant demeanor, indicating that significant events are unfolding. The focus then shifts to Lewis, who is actually Narcisse Poitou, a man with a colorful past who has adopted an English persona. As he engages with his surroundings, it becomes apparent that he is involved in a plot revolving around royalty and significant financial stakes connected to the impoverished noble class. His interactions with Senora, a character who exhibits a mix of aloofness and shrewdness, hint at a dynamic relationship that evolves through their shared ambitions, specifically regarding a scheme to obtain two hundred million francs in exchange for renouncing a crown. This intricate blend of personal and political intrigue, along with character development, indicates a rich tapestry of storytelling that delves into the complexities of power, identity, and human connection. (This is an automatically generated summary.)
Release date is 2008-03-10
Produced by Tapio Riikonen
Keywords: Paris (France) -- Fiction